Defining the Boundaries of Orthodoxy: Eunomius in the Anti-Jewish Polemic of his Cappadocian Opponents - Shepardson, Christine (Church history, 2007)
Scholars have long recognized that the theological arguments of Basil of Caesarea, Gregory of Nazianzus, and Gregory of Nyssa against their opponent Eunomius helped to shape the development of Christian orthodoxy, and thus Christian self-definition, in the late fourth-century Roman Empire. The cultural and theological significance of the strong anti-Judaizing rhetoric contained within these Cappadocian authors’ anti-Eunomian treatises, however, remains largely unexamined. Recent scholarship has demonstrated the critical role of anti-Judaizing rhetoric in the arguments that early Christian leaders Athanasius of Alexandria and Ephrem of Nisibis used against “Arian” Christian opponents in the middle of the fourth century, and the implications of this rhetoric for understanding early Christian-Jewish and intra-Christian relations. Scholars have yet to recognize, however, that anti-Judaizing rhetoric similarly helped to define the terms and consequences of the anti-Eunomian arguments made by Basil, Gregory, and Gregory in the decades that followed. The anti-Judaizing rhetoric of their texts attests to the continuing advantages that these leaders gained by rhetorically associating their Christian opponents with Jews. By claiming that Eunomius and his followers were too Jewish in their beliefs to be Christian, and too Christian in their behaviors to be Jewish, Basil, Gregory, and Gregory deployed anti-Judaizing rhetoric to argue that Eunomians were significantly inferior to both true Christians and Jews. The Cappadocians’ strategic comparisons with Jews and Judaism rhetorically distanced their Eunomian opponents from Christianity and thus strengthened the Cappadocians’ own claims to represent Christian orthodoxy.